Behaviors of phase diagrams of Ising model with competing ternary and binary interactions on a Cayley tree of arbitrary order - Akin, Hasan; Ganikhodjaev, Nasir; Uguz, Selman; Temir, Seyit (Polish Academy of Sciences Publishing House, 2012)
An Ising model with competing interactions has recently been studied extensively because of the appearance of nontrivial magnetic orderings. In this paper, we study the phase diagrams for the Ising model on a Cayley tree with competing nearest-neighbor interactions J and ternary prolonged interactions Jtp on a Cayley tree of arbitrary order k and compare with the phase diagrams obtained in Uguz et al. and Vannimenus results for the Ising model on a Cayley tree with competing nearest-neighbor interactions J and ternary prolonged interactions Jp. For some values of k, we obtain phase diagrams of the model. We clarify the role of order k of the Cayley tree. We also plot the variation of the wave vector with temperature.